Capital Structure and Its Implication on Profitability: An Empirical Study from Sharia Banks in Indonesia - Dadan Rahadian; Zahara Fitri Ramandhini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Profitability is one of the business goals that need to be achieved to ensure sustainability, as well as a chance to expand. Capital structure is the subject of an interesting discussion in determining profitability. This study aims at examining the influence of capital structure on profitability in sharia banks in Indonesia in which the management of sharia banks is different from conventional banks. A capital structure used in this study comprises the Debt-to-Equity Ratio (DER) and Debt-to-Asset Ratio (DAR), while profitability comprises Return-on-Equity (ROE) and Return-on-Asset (ROA) in sharia banks in Indonesia for five years. The findings revealed that there was no significant influence between capital structure and profitability in sharia banks in Indonesia, both measured using DER, DAR on ROE, and ROA. This study implies that the findings are different from previous studies, but the results of the correlation coefficient show a negative direction. In other words, the higher the use of debt, the lower the profitability. The use of debt that is too high can reduce the level of profitability, and not produce assets at the optimal point. Therefore, the composition of debt in sharia banks needs special attention to increase the expected profit.